All‐oral direct‐acting antiviral therapy in HCV‐advanced liver disease is effective in real‐world practice: observations through HCV‐TARGET database. Issue 1 (28th October 2016) - Reddy, K. R.; Lim, J. K.; Kuo, A.; Di Bisceglie, A. M.; Galati, J. S.; Morelli, G.; Everson, G. T.; Kwo, P. Y.; Brown, R. S.; Sulkowski, M. S.; Akuschevich, L.; Lok, A. S.; et al.
Summary: Background: Chronic hepatitis C virus therapy in patients with advanced liver disease remains a clinical challenge. HCV‐TARGET collects data in patients treated at tertiary academic and community centres. Aim: To assess efficacy of all‐oral HCV therapy in advanced liver disease. Methods: Between December 2013 and October 2014, 240 patients with a MELD score of ≥10 initiated HCV treatment with an all‐oral regimen. Data from the 220 patients who completed 12‐week follow‐up were analysed. Results: Genotype 1 (GT1) patients had higher sustained virological response (SVR) when treated with sofosbuvir plus simeprevir ± ribavirin than with sofosbuvir plus ribavirin (66–74% vs. 54%); GT1b vs GT1a (84% vs. 64%). SVR for GT2 was 72% with sofosbuvir plus ribavirin, while GT3 patients had a substantially lower response (35%). A decrease in MELD score was not clearly related to SVR over the short course of follow‐up although some had improvements in MELD score, serum bilirubin and albumin. A predictor of virological response was albumin level while negative predictors were elevated bilirubin level and GT1a. Most patients with GT1 were treated with approximately 12‐week duration of sofosbuvir and simeprevir ± ribavirin therapy while GT2 and GT3 patients were treated with approximately 12 and 24 weeks of sofosbuvir plus ribavirin respectively. Conclusions: All‐oral therapies are effective among patients with advanced liver disease with high levels of success in GT2 and GT1b, and may serve to reduce the severity of liver disease after SVR. Treatment for GT3 patients remains an unmet need. Clinical trial number: NCT01474811